If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 9n + -12 Reorder the terms: 15 = -12 + 9n Solving 15 = -12 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 15 + -9n = -12 + 9n + -9n Combine like terms: 9n + -9n = 0 15 + -9n = -12 + 0 15 + -9n = -12 Add '-15' to each side of the equation. 15 + -15 + -9n = -12 + -15 Combine like terms: 15 + -15 = 0 0 + -9n = -12 + -15 -9n = -12 + -15 Combine like terms: -12 + -15 = -27 -9n = -27 Divide each side by '-9'. n = 3 Simplifying n = 3
| 12m=28-2m | | n+35= | | 9x^2-17x=2 | | 8+5v=3v+32 | | 2h+19=8h(-5) | | 7x^2-4x-56=0 | | 5r^2+23+26= | | 6ln(4x+8)=12 | | 6y-9u=6(-2)+u | | 9(y-4)/5=2y-3 | | 12r^2s-3sr=x | | 128=4x-8 | | 3c/4=6 | | 3a+5b=53 | | (x)^(3/2)=8 | | 3log(4x+4)=14 | | 3x+5y=53 | | 4u-9u=6(-2)+u | | 12.5-8.5=-20 | | f(x)=2sin^2(x) | | 3m+45=120 | | 64x^2-48x-16=0 | | -8*1.2+0.4y=3 | | x+.5x+8=7(x+4.5) | | 15n+3-3n=39 | | 3ln(4x+4)=14 | | -3E+5E=29-2-7E | | 25x^2+16x^2=9 | | -2x-5=-2x-3-2 | | -8x+7x=3+x | | -8*12+0.4y=3 | | 12=8m-12 |